Pengaruh Penggunaan Model Contextual Teaching and Learning (CTL) Terhadap Hasil Belajar Penjumlahan dan Pengurangan Pecahan di Kelas V SD Gugus IV GugukPanjang Kota Bukittinggi - Sari, Reza Novita; Masniladevi, Masniladevi; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of the this research was to know the effect of the use of Contextual Teaching and Learning (CTL) learning models on the learning outcomes of addition and subtraction of fractions in class V SD. This research design is quasi experiment with nonequivalent control group design. The sample in this study is class V SDN 05 Tarok Dipo as a Conventional class and SDN 16 Tarok Dipo as a class CTL. The results showed that there were differences in students' mathematics learning outcomes using Conventional models with the CTL Guguk Panjang Cluster IV model in Bukittinggi City. This is evidenced by the results of tcount 1,96 and t table at a significance level of 0,05 at 1,68595, so that t count> t table.